La situation sociolinguistique de l’irlandais - Anders Ahlqvist (La Bretagne Linguistique, 1998)
The sociolinguistic situation of Irish is characterised by a very significant and early decline in the number of its speakers, as a consequence of the English domination of the country. Whereas in 1800, English was only used in a few urban areas in the East of the island, by 1851, i.e. after the Great Famine, Irish was no longer the majority language but in three large regions in the West (from Donegal to Kerry), with no more territorial continuity. However, the gradual emancipation of the country, until its complete independence after the First World War, allowed Irish to regain a place in official and state use. The resulting development of new norms is nonetheless not without its problems. As for the large-scale revitalisation of Irish, it also remains a challenge, sometimes pitting collective against individual interest in mastering the language.